2015
DOI: 10.1001/jamaophthalmol.2015.1119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Uveal Melanoma in Patients With GermlineBAP1Mutations

Abstract: IMPORTANCE Somatic mutations in BAP1 (BRCA1-associated protein 1 gene) are frequently identified in uveal melanoma. To date, the role of germline BAP1 mutations in uveal melanoma has not been characterized. OBJECTIVE To characterize the clinical phenotype of uveal melanoma in patients with germline BAP1 mutations. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study at an academic ophthalmology referral center among 507 patients with uveal melanoma who consented for collection of blood samples. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 35 publications
1
93
0
Order By: Relevance
“…Eighteen of 174 (10%) of the reported patients with germline BAP1 mutations had RCC with median age of diagnosis earlier than that seen in the general population (Table 1) (3, 5, 18, 25, 29, 37–40). Tumor tissue studies demonstrating LOH, somatic BAP1 mutations, and IHC staining all support an association between germline BAP1 mutation and RCC (Table 1) (39, 40, 44, 5560).…”
Section: Resultsmentioning
confidence: 98%
“…Eighteen of 174 (10%) of the reported patients with germline BAP1 mutations had RCC with median age of diagnosis earlier than that seen in the general population (Table 1) (3, 5, 18, 25, 29, 37–40). Tumor tissue studies demonstrating LOH, somatic BAP1 mutations, and IHC staining all support an association between germline BAP1 mutation and RCC (Table 1) (39, 40, 44, 5560).…”
Section: Resultsmentioning
confidence: 98%
“…Njauw et al have demonstrated that BAP1 mutations are more frequent among metastatic UM cases compared to non-metastatic UM controls (8% vs. 0%, p = 0.059), which has subsequently been confirmed in a separate cohort of 507 patients with OM. 5, 16 In addition, BAP1 mutations were more common in families with both CMM and UM compared to those with only CMM (29% vs. 0.52%; p= 0.003). 5 Gupta et al have recently reported that patients with UM, positive for germline BAP1 mutations, developed larger tumors (mean diameter, 15.9 vs 12.3 mm), exhibited higher rates of ciliary body involvement (75.0% vs 21.6%), had a higher metastatic potential (71.4% vs 18.0%) and had an increased frequency of family cancer history (especially for CM and OM) compared to controls.…”
Section: 2 Bap1 Tumor Syndromementioning
confidence: 97%
“…Similar to Li-Fraumeni syndrome (33), there are a number of reported BAP1 mutation families where individuals are afflicted with more than one type of primary tumor (23,(42)(43)(44), strongly suggesting multiple tissue lineages being targeted by BAP1 deficiency. Cancer incidence data from published papers reporting germline BAP1 mutations indicated that the two most common primary tumors observed together are MM and UM (7 cases), melanocytic tumors and CM (7 patients), CM and basal cell carcinoma (7 patients), and MM and CM (6 cases) ( Table 1).…”
Section: Unique MM Clinical Characteristics Associated With Bap1 Mutamentioning
confidence: 99%